Developing critical thinking and problem solving skills through skill-enhancing game / Nor Aishah Abdullah - Nor Aishah , Abdullah (2018)
Reasoning is believed as one of the core characteristics of chess game. Player of the game tend to break down big problems to smaller pieces and then put them back together. Although various schemes and programs have been put into action in the U.S., Canada and some European countries, playing chess is merely regarded as hobby when it should be exploited for increasing child’s ability to think critically. This research is an experimental research in observing students’ development in critical thinking skills through chess playing. Participants were divided into two groups of student age 10 years old. The first group comprised of students with the ability to play the game and the second group consisted of students who have no prior knowledge of the rules or the strategies of such games. Both groups were subjected to pre-test and post-test involving solving problems in Mathematics, Science, and Critical Thinking test. After 10 weeks of chess intervention, data were analyzed using t-test to compare the mean differences between two groups, and Pearson’s test to see correlation between two variables; critical thinking and science, critical thinking and mathematics. Results have shown that chess has the potential as a good tool to develop students’ critical thinking skills, although different set of students demonstrate different result. Larger sample size and longer duration of experiment could demonstrate a better result in participants’ scores and this can take into consideration for future research.